Estimating the COVID-19 Prevalence in Spain With Indirect Reporting via Open Surveys - Augusto Garcia-Agundez; Oluwasegun Ojo; Harold A. Hernández-Roig; Carlos Baquero; Davide Frey; Chryssis Georgiou; Mathieu Goessens; Rosa E. Lillo; Raquel Menezes; Nicolas Nicolaou; Antonio Ortega; Efstathios Stavrakis; et al. (Frontiers Media S.A., 2021)
During the initial phases of the COVID-19 pandemic, accurate tracking has proven unfeasible. Initial estimation methods pointed toward case numbers that were much higher than officially reported. In the CoronaSurveys project, we have been addressing this issue using open online surveys with indirect reporting. We compare our estimates with the results of a serology study for Spain, obtaining high correlations (R squared 0.89). In our view, these results strongly support the idea of using open surveys with indirect reporting as a method to broadly sense the progress of a pandemic.